Characteristic Of Co-Polyamide Nanofiltration Membrane : Effect Of Reaction Time - Ahmad, A. L.; Ooi, B. S.; Zulkali, M. M. D.; Choudhury, J. P. (2004)
Modified polypiperazinamide polyamide nanofiltration membranes were fabricated under different reaction time. The membranes were characterized for its pore size and effective thickness/porosity using Donnan Steric Pore Flow Model. It was found that the pore size and crosslinking extent was different from what normally observed in polypiperazinamide membrane. Pore size was reduced initially due to the crosslinking process but become larger at longer reaction time because of the weaker pores wall. On the other hand, the effective thickness/porosity grows exponentially with polymerization time. The effect of reaction time on pore size is not as significant as effective thickness/porosity. Within 2 minutes of polymerization time, the effective thickness of the barrier layer would vary about 150%.